Innovations in Occupational Safety Training - Valentinovna, Kotova Lyubov; Tursunova, Elza Akramovna (European Journal of Life Safety and Stability (2660-9630), 2022)
The article attempts to analyze modern innovative approaches to occupational safety training. It is shown that innovative technologies in occupational safety training are aimed at optimizing and improving the effectiveness of training.